Security and privacy challenges in mobile cloud computing: Survey and way ahead - Mollah, Muhammad Baqer; Azad, Md. Abul Kalam; Vasilakos, Athanasios (Journal of network and computer applications, 2017)
The rapid growth of mobile computing is seriously challenged by the resource constrained mobile devices. However, the growth of mobile computing can be enhanced by integrating mobile computing into cloud computing, and hence a new paradigm of computing called mobile cloud computing emerges. In here, the data is stored in cloud infrastructure and the actual execution is shifted to cloud environment so that a mobile user is set free from resource constrained issue of existing mobile devices. Moreover, to avail the cloud services, the communications between mobile devices and clouds are held through wireless medium. Thus, some new classes of security and privacy challenges are introduced. The purpose of this survey is to present the main security and privacy challenges in this field which have grown much interest among the academia and research community. Although, there are many challenges, corresponding security solutions have been proposed and identified in literature by many researchers to counter the challenges. We also present these recent works in short. Furthermore, we compare these works based on different security and privacy requirements, and finally present open issues.